A new species of the genus Puto Signoret (Hemiptera: Coccomorpha: Putoidae) from China and redescription of Puto huangshanensis Wu - Zheng, Xinyi; Li, Yuang; Tan, Zhixiang; Wu, San’an (Zootaxa, 2025)
The scale insect genus Puto Signoret (Hemiptera: Coccomorpha: Putoidae) has a mainly Nearctic and Palaearctic distribution but one species is known from Oriental China and a second from the Palaearctic part of China prior to this study. Here we describe and illustrate the adult female and male of a new species, Puto sinensis Zheng & Wu, sp. nov., from Oriental China. We also redescribe and illustrate the adult female and male of Puto huangshanensis Wu, 2001 and provide diagnostic characters for both species. In addition, an identification key to the Old World species of Puto based on the adult female, and a key to the world adult males of Puto are provided.